A case report of extensive condyloma acuminata in a pediatric patient clearing with compounded 3% cidofovir gel - Ben Wroblewski; Fabiana Castro Porto Silva Lopes; William David Boothe; Lucia Z. Diaz (SpringerOpen, 2023)
Abstract Background Management and treatment of condyloma acuminata in children are often challenging. The mode of transmission is not always traceable and a sexual abuse investigation should be considered. Treatment ranges from no intervention to reconstructive surgery depending on the extent and symptoms. Case presentation We are reporting a case of an 18-month-old female with extensive symptomatic condyloma acuminata who was able to avoid surgical treatment after treatment with topical cidofovir 3% gel. Conclusion This patient is being presented to highlight a medical treatment that can be considered in extensive or large condyloma acuminata cases.